2013
DOI: 10.2528/pierc12112012
|View full text |Cite
|
Sign up to set email alerts
|

Archimedean Spiral Antenna With Band-Notched Characteristics

Abstract: Abstract-A coplanar waveguide (CPW)-fed Archimedean spiral antenna with band notched characteristics is presented for ultrawideband (UWB) applications. The proposed antenna consists of a two-arm spiral fed by a CPW line. The novelty of this design is integrating three inverted U-shaped slots within the feeding line of the spiral antenna to introduce frequency band notched characteristics at 5.8 GHz. This antenna covers the frequency range from 3.1 GHz to 10.6 GHz with VSWR less than 2, except at a band rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recently, it has been reported that stopbands are generated for the spiral antennas [15][16][17][18][19][20][21]. The spiral antennas in refs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that stopbands are generated for the spiral antennas [15][16][17][18][19][20][21]. The spiral antennas in refs.…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [18,19], a CPW spiral antenna that has one stopband created without vias has been reported, where the radiation is bi-directional. A U-slot is cut into a CPW transmission line to generate one stopband.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, selective type of antenna to be used in every miniaturize electronics gadget is also in growing interest toward microstrip antenna. The main advantages of microstrip antenna are low profile, low cost, easy to manufacture, and light weight . However, microstrip antenna possesses drawbacks of low gain, low efficiency, and narrow bandwidth .…”
Section: Introductionmentioning
confidence: 99%